(untitled) (Revista de Ciências Agroveterinárias, 2012)
The raspberry (Rubus idaeus L.) is a temperate climate fruit, which together with the blackberry (Rubus sp.), is distinguished in the small fruits market in recent years. Due to the low implementation cost and maintenance of the orchard and high yield per hectare, the culture has aroused the interest of family farmers. The usual way of propagation is by cuttings, or woody tissue culture. The objective was to evaluate the technique of propagation by root cuttings of two cultivars of raspberry, Batum and Heritage. Cuttings, five inches long and three to four millimeters in diameter, were taken and then planted in a greenhouse until two pairs of leaves appeared. The number and length of the roots from the corm, branch height, number of leaves and buds was evaluated. Propagation by root cuttings is viable for both cultivars.